2018
DOI: 10.1016/j.microc.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Protecting and stimulating effect on the degradation of eosin lakes. Part 1: Lead white and cobalt blue

Abstract: An important problem encountered during the preservation of paintings and other artworks is the fading of the original colors due to exposure of the colorants to light. This fact is clearly evidenced in some of Vincent Van Gogh's paintings in which an organic red, eosin or geranium lake, is present.The identification of eosin and the characterization of its degradation products in paintings represents a challenge because of (i) the generally low concentration of the pigment remaining after an aging period of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 31 publications
4
21
0
Order By: Relevance
“…In a first explorative experiment, ATR-FTIR analysis was carried out to confirm the formation of the lake pigment after the synthesis, , Figure S2. During the artificial photoaging, FORS spectroscopy analysis (Figure S3) was used to follow the color changes occurring during the discoloration process observed on the paint models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a first explorative experiment, ATR-FTIR analysis was carried out to confirm the formation of the lake pigment after the synthesis, , Figure S2. During the artificial photoaging, FORS spectroscopy analysis (Figure S3) was used to follow the color changes occurring during the discoloration process observed on the paint models.…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been demonstrated that the original colors used by Van Gogh are losing their brightness, particularly, when eosin lakes are present . This may be because eosin is a photosensitizer , and its degradation mechanism can be strongly affected by the surrounding media, leading to the discoloration of masterworks within an artist’s lifetime . In this context, it is also very relevant to have a full understanding of the mechanism of breakdown and discoloration of the original molecules, as such knowledge can be used to design optimal conditions of storage and display of the art works.…”
mentioning
confidence: 99%
“…Both molecular fluorescence and reflectance imaging spectroscopy could detect eosin lake in the presence of a white pigment, even at the lowest concentrations prepared (approximately 0.033 %, Figure ), and thus the detection limit of these respective techniques was not reached. With reflectance spectroscopy, white pigments cause increased light scattering within the paint volume and increase the chance for detection of the red lake . With XRF imaging spectroscopy, Br was clearly detected at an eosin lake concentration of 1 % by mass but was not detected at the lowest concentrations prepared, even though these paint samples are visibly pink.…”
Section: Discussionmentioning
confidence: 99%
“…1 Optics Department, Faculty of Sciences, University of Granada, Granada, Spain. 2 Painting Department, Faculty of Fine Arts, University of Granada, Granada, Spain. 3 Analytical Chemistry Department, Faculty of Sciences, University of Granada, Granada, Spain.…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
“…Spectral imaging is an emerging tool in analysis in the field of conservation and restoration of Cultural Heritage (CH) [1,2]. Some of the most relevant applications found are the identification of pigments and materials used in the original artworks [3,4], the characterization of the preservation state using spectral ranges beyond the visible [5] and the visualization of hidden layers or "pentimenti" using the infrared range [6].…”
Section: Introductionmentioning
confidence: 99%